2000
DOI: 10.1149/1.1393527
|View full text |Cite
|
Sign up to set email alerts
|

Rate Theory of Multicomponent Adsorption of Organic Species on Silicon Wafer Surface

Abstract: Advanced electronic devices currently have a serious problem in their fabrication process due to the presence of organic hydrocarbon contamination on the silicon wafer surface. [1][2][3][4][5][6][7] To develop the technology to achieve a sufficiently clean silicon wafer surface, many kinds of organic species existing on the silicon wafer surface have been studied, such as propionic (propanic) acid ester, 8 trimethyl silanol, 9 hexamethyl disiloxane, 9 cyclosiloxanes (D3-D11), 8-10 trichloroethyl phosphate, 9,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(82 citation statements)
references
References 9 publications
7
74
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16] Assumption 1: There is quite small interaction between organic molecules in gas phase and on silicon surface. Assumption 2: Organic molecules are physisorbed on silicon surface due to very weak interactions between organic molecule and the silicon surface.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (12) P4mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] Assumption 1: There is quite small interaction between organic molecules in gas phase and on silicon surface. Assumption 2: Organic molecules are physisorbed on silicon surface due to very weak interactions between organic molecule and the silicon surface.…”
Section: Ecs Journal Of Solid State Science and Technology 4 (12) P4mentioning
confidence: 99%
“…8 The information obtained by the QCM could be understood by using the Multi-Component Organic Species Adsorption-Induced Contamination (MOSAIC) model in our previous studies [9][10][11][12][13][14][15][16] using isopropanol (IPA), octanol (OCT) and diethylphthalate (DEP). In previous studies, [13][14][15][16] the molecular interaction was found to be not significant among the IPA, OCT and DEP.…”
mentioning
confidence: 99%
“…Using the MOSAIC model [9], the time-dependent adsorption and desorption behavior of chemical compounds on a surface is described as follows:…”
Section: Model 1: Multi-component Systemmentioning
confidence: 99%
“…For this purpose, the complicated adsorption and desorption behaviors of organic compounds on a silicon surface have been studied [9][10][11][12][13][14] using the in situ measurement method of the quartz crystal microbalance (QCM) and the rate theory of the multi-component organic species adsorption-induced contamination (MOSAIC) model [9]. As an extension, the authors studied the acetic acid (ACA) behavior [15] on a silicon surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by linking it with the rate theory, such as the multicomponent organic species adsorption-induced contamination (MOSAIC) model, [9][10][11][12][13][14][15] the molecular radii of the organic molecules can be evaluated along with the rate parameters of physisorption and desorption. Additionally, this analysis could determine the molecular radii and their summation at the surface for showing the attraction and repulsion between the molecules in a multicomponent system.…”
mentioning
confidence: 99%